GONÇALVES, J. C. et al. (org.). Além da tese: percursos de pesquisa em ciências humanas. São Paulo: Hucitec, 2022. 212 p. - Cavalcante, Claudia Garcia (Bakhtiniana. Revista de Estudos do Discurso, 2022)
Resenha